A management model for archaeological site museums in Turkey - Erturk, Nevra (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2006)
Archaeological site museums play an important role in the protection of the world's cultural heritage. Turkey, which is a country rich with traces of many world civilizations, has five archaeological site museums. These museums, however, require sustainable and effective management plans in order to realize properly on-site preservation, documentation, research, exhibition and interpretation, as well as to raise public awareness and to provide an economic income for the locals. In this context, this paper aims to define the current situation of archaeological sites and museums with a focus on archaeological site museums in Turkey; to discuss the role of archaeological site museums in the protection of cultural heritage, as well as their management difficulties, and will conclude with a management model for archaeological site museums in Turkey. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: Archaeological site museum; Archaeological site management; Movable cultural heritage; Museum management; Sustainable management; Arts & Humanities - Other Topics